A photo-responsive fluorescent amphiphile for target-specific and image-guided drug delivery applications. Issue 39 (26th September 2022) - Dey, Subhasis; Sen, Plaboni; Patel, Anjali; Prusty, Biswa Mohan; Ghosh, Siddhartha Sankar; Manna, Debasis
Abstract : CYsome: an acetazolamide grafted cyanine-3-based macrocyclic amphiphile demonstrates target-specificity, biocompatibility, self-imaging, and a NIR-responsive release profile for image-guided chemotherapeutic applications. Abstract : Multifunctional drug delivery systems are the centerpiece of effective chemotherapeutic strategies. Herein, we report the synthesis of an acetazolamide-linked cyanine-3-based NIR-responsive fluorescent macrocyclic amphiphile that self-assembled into spherical nanostructures in the aqueous medium via a J-aggregation pattern. The amphiphile shows various favorable properties of lipids. The photocleavage of the strained dioxacycloundecine ring induces spherical to nanotubular self-assembly with concomitant release of an encapsulated anticancer drug, doxorubicin (Dox), in a controlled manner. The CA-IX targeted amphiphile also showed lower cytotoxicity, effective cellular uptake, and Dox delivery to the model carcinoma cells.